Absence of middle colic artery from the superior mesenteric artery - Reshma Betal; Sibani Mazumdar; Ardhendu Mazumdar (Wolters Kluwer Medknow Publications, 2016)
The knowledge of branches of superior mesenteric artery important for Surgeon and radiologists who deals abdominal diseases. Superior mesenteric artery is second ventral branch of abdominal aorta which arises from 1 cm below coelic trunk, opposite L1 vertebrae and supplies lower portion of duodenum, whole jejunum, ileum caecum, appendix, ascending colon and major portion transverse colon. Actually it is the artery for derivates of midgut. [1] Superior mesenteric artery gives inferior pancreatic duodenal artery, middle colic artery, right colic artery and ileo colic artery from its right concave side some ileo-jejunal artery from convex left side. Usually middle colic artery arises from superior mesenteric artery at the lower border of pancreas and immediately enters the root of transverse mesocolon and divides into right and left branch. The right branch anastomose with ascending branch of right colic artery near right colic flexure and left anastomose with ascending branch of left colic. Here we present a case of absence of mid colic artery from superior mesenteric artery and right colic artery shows some extra branches from its proximal part which supplies transverse colon.